A review of the potential effects of climate change on disseminated neoplasia with an emphasis on efficient detection in marine bivalve populations - Bramwell, Georgina; Schultz, Aaron G.; Sherman, Craig D.H.; Giraudeau, Mathieu; Thomas, Frédéric; Ujvari, Beata; Dujon, Antoine M. (The Science of the total environment, 2021)
Climate change not only directly impacts marine environments by shifting water temperatures, salinity, pH and dissolved oxygen concentrations, but may also indirectly contribute to the emergence of additional ecosystem stressors, such as infectious diseases, including bivalve disseminated neoplasia. Disseminated neoplasia, a form of cancer found in some bivalves - recently discovered to be transmissible in at least six species - has been shown to impair bivalve health and fitness, with occasional mass outbreaks causing high levels of mortality. As the ability of the host bivalve to respond to disseminated neoplasia, and the survival and transmissibility of disseminated neoplasia both depend on environmental factors, it is crucial to understand the interaction between climate change and disseminated neoplasia epidemiology. Furthermore, with bivalves being species of high ecological and economic importance, there is a rising need for the development of efficient disseminated neoplasia diagnostic tools in order to detect, mitigate and potentially prevent deleterious disseminated neoplasia outbreaks. Therefore, in this study, we reviewed the current knowledge of climate impacted environmental parameters on disseminated neoplasia and identified best practices and methodology for the detection of transmissible disseminated neoplasia in the wild. By exploring the potential effects changing climate has on disseminated neoplasia dynamics, we identified future research directions in order to advance the field. This included using state of the art disease detection methods and taking into account species' ecological niches to understand the dynamic of disseminated neoplasia outbreaks in the wild and to investigate whether disseminated neoplasia is present in freshwater ecosystems. Finally, we provided a comprehensive step-by-step guideline for an evidence-based detection of this disease in marine ecosystems. [Display omitted] •Ocean warming is likely to favour disseminated neoplasia outbreaks.•The effect of seasonality on disseminated neoplasia seems species specific.•Detailed prevalence and environmental data are required to understand outbreak dynamics.•State of the art detection methods will be of key importance to obtain insights.